A narrative approach: English learning strategies amongst EFL students - Ismiatun, Febti; Ni’mah, Dzurriyyatun; Widowati, Diah Retno (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Language Learning Strategies (LLSs) are trusted to be an influential factor affecting the students’ success in English learning. Among the myriads researchers have conducted study on this issue through various perspectives. Inspired from three successful language students, this current study was carried out to highlight the students’ attitudes towards the role of learning strategies, the recommended and non-recommended strategies in the process of learning, and the other contributing factors affecting the EFL learning. To fill the burgeoning need of the study, a narrative approach was undertaken to bring the study on the issue. Likewise, a series of question were addressed to reach the goal of the study through an open-ended interview. Subsequently, the result of interview was transcribed and interpreted through thematically analyses (Creswell & Poth, 2018). It uncovered that the participated students have positive attitudes towards English learning strategies. They enlightened several good strategies that shape their English skills, such as utilizing YouTube video, building a high confidence, and practicing English in a single language. On the other hand, they also put in the picture that memorization became the most common ineffective strategy. As the last finding, the students perceived that technology, learning environment, society, and personal condition are other factors boosting the achievement in English learning. The finding of the study presents the practical benefit to the practitioners, researchers, and policy makers.